2022
DOI: 10.1111/jocn.16281
|View full text |Cite
|
Sign up to set email alerts
|

Why breast cancer patients avoid communicating disease‐related information to their dependent children: A qualitative study

Abstract: Aim and objectives: This qualitative study explores why breast cancer patients do not share disease-related information with their dependent children.Background: 'Open' communication between breast cancer patients and their children is beneficial to both. However, some still try to avoid discussing their diagnosis and related information with their children. Some worries lie in communicating with dependent children, but the underlying cause remains unclear.Design: Qualitative descriptive study.Methods: Semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“… Meta-themes Category Results The impact of parents'disease on their children Worrying about the physical and mental health of children Cancer may be passed on to children ( Davey et al, 2012 ; Zhu et al, 2022 ; Huang et al, 2020 ); Separation anxiety in young children, lack of self-confidence and escapism in adolescents ( Chin et al, 2021 ; Lundquist et al, 2020 ; Steiner et al, 2020 ; Elmberger et al, 2005 ; Chin et al, 2021 ; Davey et al, 2012 ; Stiffler et al, 2008 ; Shands and Lewis, 2021 ); Physical changes in parents with cancer lead to fear, low self-esteem and self-doubt in children ( Check et al, 2017 ; Tamura et al, 2021 ; Zhu et al, 2022 ; Asbury et al, 2014 ; Chin et al, 2021 ). Worrying about the life and future of their children A parent's cancer diagnosis can rob a child of a happy childhood ( Kissil et al, 2014 ; Lundquist et al, 2020 ; Zhang et al, 2023 ; Campbell-Enns and Woodgate, 2013 ); Parents rush to teach their children life skills ( Loggers et al, 2019 ; Lundquist et al, 2020 ; Park et al, 2017 ); Children's excessive worry about their parents' illnesses leads to poor academic performance or even dropping out of school ( Zhu et al, 2022 ; Huang et al, 2020 ; Zhang et al, 2023 ; Wang et al, 2020 ; Lundquist et al, 2020 ); Decreased participation of children in recreational and social activities ( Kim et al, 2012 ; Park et al, 2017 ; Huang et al, 2020 ); Children may associate with the wrong crowd ( Lundquist et al, 2020 ; Huang et al, 2020 ); Children miss the opportunity to find a suitable partner bec...…”
Section: Resultsmentioning
confidence: 99%
“… Meta-themes Category Results The impact of parents'disease on their children Worrying about the physical and mental health of children Cancer may be passed on to children ( Davey et al, 2012 ; Zhu et al, 2022 ; Huang et al, 2020 ); Separation anxiety in young children, lack of self-confidence and escapism in adolescents ( Chin et al, 2021 ; Lundquist et al, 2020 ; Steiner et al, 2020 ; Elmberger et al, 2005 ; Chin et al, 2021 ; Davey et al, 2012 ; Stiffler et al, 2008 ; Shands and Lewis, 2021 ); Physical changes in parents with cancer lead to fear, low self-esteem and self-doubt in children ( Check et al, 2017 ; Tamura et al, 2021 ; Zhu et al, 2022 ; Asbury et al, 2014 ; Chin et al, 2021 ). Worrying about the life and future of their children A parent's cancer diagnosis can rob a child of a happy childhood ( Kissil et al, 2014 ; Lundquist et al, 2020 ; Zhang et al, 2023 ; Campbell-Enns and Woodgate, 2013 ); Parents rush to teach their children life skills ( Loggers et al, 2019 ; Lundquist et al, 2020 ; Park et al, 2017 ); Children's excessive worry about their parents' illnesses leads to poor academic performance or even dropping out of school ( Zhu et al, 2022 ; Huang et al, 2020 ; Zhang et al, 2023 ; Wang et al, 2020 ; Lundquist et al, 2020 ); Decreased participation of children in recreational and social activities ( Kim et al, 2012 ; Park et al, 2017 ; Huang et al, 2020 ); Children may associate with the wrong crowd ( Lundquist et al, 2020 ; Huang et al, 2020 ); Children miss the opportunity to find a suitable partner bec...…”
Section: Resultsmentioning
confidence: 99%
“…We found that changed family roles due to a mother's breast cancer diagnosis impacted adolescents. Previous research found that mothers experience various challenges in interacting with adolescents about breast cancer due to feelings of guilt, uncertainty about their own life span and how to respond to adolescents' curiosity, and being a mother or patient, leading them to underestimate and ignore adolescents' thoughts and wishes 21,22,24 . Zahlis 67 and Mazaheri et al 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that mothers experience various challenges in interacting with adolescents about breast cancer due to feelings of guilt, uncertainty about their own life span and how to respond to adolescents' curiosity, and being a mother or patient, leading them to underestimate and ignore adolescents' thoughts and wishes. 21,22,24 Zahlis 67 and Mazaheri et al 22 reported that mothers who usually notice small changes in their children's behavior could fail to notice changes due to their shock at a breast cancer diagnosis. Tavares et al 68 report that mothers need support in communicating with their children and dealing with their children's responses and difficult questions related to breast cancer.…”
Section: Supporting Parents May Support Adolescentsmentioning
confidence: 99%
See 2 more Smart Citations